2020
DOI: 10.15294/jpii.v9i1.22362
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Generation, Evaluation, and Modification-Cooperative Learning (Gem-Cl) Model Selaras Bakar Batu Cultural Practice in Papua

Abstract: This study intended to describe the effectiveness of the GEM-CL learning model selaras Bakar Batu cultural practice on chapter heat and temperature. This type of research was quasi-experiment with pretest and post-test control group design. The study population was all students of class XI IPA SMAN 1 Jayapura. The sampling technique used was simple random sampling. The selected classes were XI IPA-3 as an experimental class and class XI IPA-5 as a control class. Data collection instruments were tests based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…This research was a type of quasi-experimental research (Budiarti et al, 2020). The design used in this study was the non-equivalent post-test only control group design.…”
Section: Methodsmentioning
confidence: 99%
“…This research was a type of quasi-experimental research (Budiarti et al, 2020). The design used in this study was the non-equivalent post-test only control group design.…”
Section: Methodsmentioning
confidence: 99%
“…Scientific literacy also closely related to problemsolving skills. Previous research found that scientific understanding related to scientific literacy in heat and temperature concepts cannot be neglected as if it is existed in comprehensive local wisdom in Bakar Batu Papua Cultural Practice (Budiarti, et al, 2020;Budiarti, 2017). The correlation in 21 st century skills with scientific literacy is very close.…”
Section: Figure 5 Scientific Literacy Model Of Gräbermentioning
confidence: 99%
“…Konsepsi ini justru sudah dimiliki oleh siswa sebelum pembelajaran (Winarti et al, 2017). Jadi Fisika merupakan bagian dari sains yang mempelajari tentang fenomena alam dan proses yang ada didalamnya (Budiarti et al, 2020). Pelajaran fisika merupakan salah satu pelajaran yang sulit dipahami oleh siswa, sehingga penanaman konsep fisika di sekolah sangatlah penting (Budiarti, 2013) (2017).…”
Section: Pendahuluanunclassified